Dynamics of Mono- and Dual-Species Biofilm Formation and Interactions Between Paracoccidioides brasiliensis and Candida albicans - Oliveira, Lariane Teodoro; Medina-Alarcón, Kaila Petronila; Singulani, Junya de Lacorte; Fregonezi, Nathália Ferreira; Pires, Regina Helena; Arthur, Rodrigo Alex; Fusco-Almeida, Ana Marisa; Mendes Giannini, Maria José Soares (Frontiers in Microbiology, 2020)
The oral cavity is a highly diverse microbial environment in which microorganisms interact with each other, growing as biofilms on biotic and abiotic surfaces. Understanding the interaction among oral microbiota counterparts is pivotal for clarifying the pathogenesis of oral diseases. Candida spp. is one of the most abundant fungi in the oral mycobiome with the ability to cause severe soft tissue lesions under certain conditions. Paracoccidioides spp., the causative agent of paracoccidioidomycosis, may also colonize the oral cavity leading to soft tissue damage. It was hypothesized that both fungi can interact with each other, increasing the growth of the biofilm and its virulence, which in turn can lead to a more aggressive infectivity. Therefore, this study aimed to evaluate the dynamics of mono- and dual-species biofilm growth of Paracoccidioides brasiliensis and Candida albicans and their infectivity using the Galleria mellonella model. Biomass and fungi metabolic activity were determined by the crystal violet and the tetrazolium salt reduction tests (XTT), respectively, and the colony-forming unit (CFU) was obtained by plating. Biofilm structure was characterized by both scanning electronic- and confocal laser scanning- microscopy techniques. Survival analysis of G. mellonella was evaluated to assess infectivity. Our results showed that dual-species biofilm with P. brasiliensis plus C. albicans presented a higher biomass, higher metabolic activity and CFU than their mono-species biofilms. Furthermore, G. mellonella larvae infected with P. brasiliensis plus C. albicans presented a decrease in the survival rate compared to those infected with P. brasiliensis or C. albicans, mainly in the form of biofilms. Our data indicate that P. brasiliensis and C. albicans co-existence is likely to occur on oral mucosal biofilms, as per in vitro and in vivo analysis. These data further widen the knowledge associated with the dynamics of fungal biofilm growth that can potentially lead to the discovery of new therapeutic strategies for these infections.